Trust or Not Trust: UnderstandÄ±ng the Effects of AllocentrÄ±sm & IdÄ±ocentrÄ±sm on Coworker Trust - Ekmekci, Ã–zge Tayfur (Journal of Economics and Behavioral Studies, 2015)
The concept of coworker trust has gained importance for the last decade due to increased teamwork and collaboration within organizations. However, there is a need to study the concept of trust with emic perspective reflecting people or societyâ€™s different values, norms and expectations. The aim of this study is to examine the role of allocentrism and idiocentrism, which represent individual level manifestations of collectivism and individualism on coworker trust and its dimension (i.e. affect- and cognition-based trust). Besides that, this study investigates whether willingness to work with somebody else is affected by cognitiveor affect-based trust. Data were gathered from German and Turkish samples and analyzed separately. Hypotheses were supported in a German sample such that allocentrism predicted both overall coworker trust and affect-based trust, while idiocentrism predicted cognition-based trust. In Turkish sample, allocentrism was found to be associated with overall coworker trust and cognition-based trust. Neither idiocentrism, nor allocentrism could predict affect-based trust in this sample. Remarkably, willingness to work with German coworkers was associated with cognitive-based trust. The results demonstrated the differential effects of idiocentrism and allocentrism on coworker trust and they are discussed together with its implications.